2015
DOI: 10.1002/oti.1385
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Fine Motor Coordination in Children Who Are Not Ready for Handwriting: Which Test Should We Take?

Abstract: When children are not ready to write, assessment of fine motor coordination may be indicated. The purpose of this study was to evaluate which fine motor test, the Nine-Hole Peg Test (9-HPT) or the newly developed Timed Test of In-Hand Manipulation (Timed-TIHM), correlates best with handwriting readiness as measured by the Writing Readiness Inventory Tool In Context-Task Performance (WRITIC-TP). From the 119 participating children, 43 were poor performers. Convergent validity of the 9-HPT and Timed-TIHM with WR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 25 publications
(63 reference statements)
1
17
1
1
Order By: Relevance
“…Also, we found a moderate correlation between the PUL score and hand function (i.e., the Nine-Hole Peg Test and Timed TIHM), indicating that both scales measure different aspects of UE function and therefore should be examined separately in clinical practices. This finding is [16]. The occurrence of contractures, i.e., decreased passive range of motion, was relatively uncommon.…”
Section: Relation Ue Function and Activitymentioning
confidence: 76%
See 3 more Smart Citations
“…Also, we found a moderate correlation between the PUL score and hand function (i.e., the Nine-Hole Peg Test and Timed TIHM), indicating that both scales measure different aspects of UE function and therefore should be examined separately in clinical practices. This finding is [16]. The occurrence of contractures, i.e., decreased passive range of motion, was relatively uncommon.…”
Section: Relation Ue Function and Activitymentioning
confidence: 76%
“…who found a moderate correlation between the Nine-Hole Peg Test and the Timed TIHM and stated that the tests measure different aspects. They found that the Timed-TIHM evaluates complex patterns, including hand manipulation skills and that the Nine-Hole Peg Test evaluates simple patterns of fine motor coordination, e.g., picking up, placing, and releasing pegs [ 16 ]. The occurrence of contractures, i.e., decreased passive range of motion, was relatively uncommon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Handwriting is a complex perceptual-motor skill that involves a combination of visualmotor coordination abilities, motor planning, cognitive, and perceptual skills, as well as tactile and kinesthetic sensitivities [4,[9][10][11]. Before children develop mature handwriting skills, they must experience several typical stages, including "drawing", "invented letters", "random letters", "transcription words", and "developmental spelling" [12].…”
Section: Introductionmentioning
confidence: 99%